The assets and liabilities gap management of conventional and Islamic banks in the organization of Islamic cooperation (OIC) countries - Poi, Hun Sun; Hassan, M. Kabir; Hassan, Taufiq; Ramadilli Mohd, Shamsher Mohamad (Taylor & Francis, 2014)
This article focuses on the short- and long-term assets and liabilities gap and the determinants of net interest/profit margins of both conventional banks and Islamic banks in the Organization of Islamic Cooperation countries over the period from 1997 to 2010. The results show that both conventional and Islamic banks have negative short-term gaps and positive long-term gaps. These indicate that banks use short-term deposits and funding to finance long-term loans, advances and investments, taking into consideration refinancing and reinvestment risks. The findings also show that operating cost is a significant determinant of bank margins and important factor to improve quality of management in banks. Overall, the conventional banks have better quality of assets and liabilities with an optimum composition of profitable assets and low-costs liabilities. The low bank margins in conventional and Islamic banks indicate low volatility in financial markets and the growth of banking business.